Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes the fiscal challenges in Lithuania. Lithuania's fiscal position has strengthened in recent years. However, medium term challenges are significant given the severe demographic pressures from population aging and net emigration. Lithuania's net financial worth of the general government is relatively strong compared with other countries in the region although contingent liabilities from the pension system are sizable. The recent reform of the pension system will help make the system more fiscally sustainable. Upcoming reforms should be carefully designed, considering their trade-offs, to ensure social sustainability; reduce old-age poverty; and limit adverse impact on labor supply and informality.